Improvement of a cashing trainer assembly methodology for FPGA development in vocational education students - Tuti Suartini; Sri Lestari Harja; Aan Sukandar (Universitas Negeri Yogyakarta, 2022)
Learning media is defined as a tool used in conveying learning messages to students. Teachers or lectures can use the media to stimulate thoughts, feelings, attention and abilities or skills, and one of them is the use of trainers. The development board FPGA of trainer tools for skill learning in digital technology-based vocational education today has been a problem that obstructs the growth of experts in high-tech-based vocational field.The Spartan development board and its software can be used to elaborate the improvement of skill learning. This research analyse how the development board can be used to enhance students’ thinking skill. The trainer tools in the market lately are still in the form of a mother board that can be interfaced with various devices commonly used to perform various digital automation technology. This study elaborates the use of the cashing trainer assembly among electrical engineering students and mechanical engineering students in a joint project to assembly a development mother board.The learning media is also used in group training among the peers.Based on trials and observations made by researchers, the students as the object of research results, have not performed optimally to combine planning of cashing trainer assembly methodology and practice in the assembly.